Frequency of telomerase reverse transcripter promoter mutations in desmoplastic melanoma subtypes: analyses of 76 cases. Issue 4 (August 2016) - Yang, Shi; Leone, Dominick; Frydenlund, Noah; Hoang, Mai; Deng, April; Hernandez-Perez, Marier; Biswas, Asok; Singh, Rajendra; Yaar, Ron; Mahalingam, Meera
Abstract : Estimates of the frequency of telomerase reverse transcripter ( TERT ) mutations in desmoplastic melanoma (DM) are limited. DM is categorized into subtypes, pure and mixed, differing in prognosis, suggesting genetic heterogeneity. Given this, our aims were to determine the incidence of TERT promoter mutations in DM subtypes and to evaluate its relationship with established histopathologic prognosticators, BRAF and RETp status, and neurofibromin protein expression. Of the archival annotated samples retrieved, 76 cases of DM (48 pure and 28 mixed) fulfilled the criteria for inclusion. PCR amplification of the TERT promoter region was performed on DNA extracted from formalin-fixed paraffin-embedded tissue using primers 5′-GCCGATTCGACCTCTCTCC-3′ (forward) and 5′-CAGCGCTGCCTGAAACTC-3′ (reverse). For each case, appropriate C>T mutations were identified on the electropherograms. Univariate analysis using χ 2 -test was carried out to identify potential confounders; a nested case–control study of demographic, clinical, histopathological, and genetic determinants was carried out using multiple logistic regression. Significant differences in TERT promoter mutation frequencies were noted in the subtypes (mixed vs. pure; 15/28, 54% vs. 11/48, 23%, respectively, P =0.0066). After adjusting for potential confounding, multivariate analyses indicated a three-fold increase in the odds of the TERT mutation for those with the mixed subtype compared with the pure subtype ( P =0.04, adjusted odds ratio =3.32). No other significant associations were noted (sex/junctional component/Breslow depth/ulceration/mitoses/host response/ RETp, BRAF status, and neurofibromin protein expression). Our findings, the largest to date investigating TERT promoter mutations in DM, support the hypothesis that the subtypes have distinct genetic drivers and underscore the relevance of telomere integrity in the etiopathogenesis of the mixed variant.